Implementation Cost Comparison of TSN Traffic Control Mechanisms - Pruski, Aleksander (2021)
The IEEE Time-Sensitive Networking (TSN) Task Group specifies a set of standards that enables real-time communication with predictable and bounded delays over the Ethernet. Specifically, TSN introduces a new set of so-called shapers, which regulate traffic arrival and transmission in the networks. Prominent among those are the IEEE 802.1 Qbv Time Aware Shaper (TAS) and IEEE 802.1Qav Credit-Based Shaper (CBS).Another traffic control mechanism is the IEEE 802.1Qbu Frame Preemption. Most works in the literature have focused on the quantitative performance comparison between these mechanisms. However, the discussion on how they compare in terms of implementation cost has received less attention. In this paper,we provide a comprehensive comparison of the implementation cost of the aforementioned TSN traffic control mechanisms. This comparison can help system designers in choosing which of the mechanism(s) to deploy for their applications.